POSNOC—POsitive Sentinel NOde: adjuvant therapy alone versus adjuvant therapy plus Clearance or axillary radiotherapy: a randomised controlled trial of axillary treatment in women with early-stage breast cancer who have metastases in one or two sentinel nodes - Wei Tan; Luke Vale; Alastair Thompson; Alan Montgomery; Sarah Craig; Vaughan Keeley; Laura Ternent; Nisha Sharma; Eleanor Mitchell; Lelia Duley; Ian Ellis; Alistair Ring; et al. (BMJ Open)
Introduction ACOSOG-Z0011(Z11) trial showed that axillary node clearance (ANC) may be omitted in women with ≤2 positive nodes undergoing breast conserving surgery (BCS) and whole breast radiotherapy (RT). A confirmatory study is needed to clarify the role of axillary treatment in women with ≤2 macrometastases undergoing BCS and groups that were not included in Z11 for example, mastectomy and those with microscopic extranodal invasion. The primary objective of POsitive Sentinel NOde: adjuvant therapy alone versus adjuvant therapy plus Clearance or axillary radiotherapy (POSNOC) is to evaluate whether for women with breast cancer and 1 or 2 macrometastases, adjuvant therapy alone is non-inferior to adjuvant therapy plus axillary treatment, in terms of 5-year axillary recurrence.Methods and analysis POSNOC is a pragmatic, multicentre, non-inferiority, international trial with participants randomised in a 1:1 ratio. Women are eligible if they have T1/T2, unifocal or multifocal invasive breast cancer, and 1 or 2 macrometastases at sentinel node biopsy, with or without extranodal extension. In the intervention group women receive adjuvant therapy alone, in the standard care group they receive ANC or axillary RT. In both groups women receive adjuvant therapy, according to local guidelines. This includes systemic therapy and, if indicated, RT to breast or chest wall. The UK Radiotherapy Trials Quality Assurance Group manages the in-built radiotherapy quality assurance programme. Primary endpoint is 5-year axillary recurrence. Secondary outcomes are arm morbidity assessed by Lymphoedema and Breast Cancer Questionnaire and QuickDASH questionnaires; quality of life and anxiety as assessed with FACT B+4 and State/Trait Anxiety Inventory questionnaires, respectively; other oncological outcomes; economic evaluation using EQ-5D-5L. Target sample size is 1900. Primary analysis is per protocol. Recruitment started on 1 August 2014 and as of 9 June 2021, 1866 participants have been randomised.Ethics and dissemination Protocol was approved by the National Research Ethics Service Committee East Midlands—Nottingham 2 (REC reference: 13/EM/0459). Results will be submitted for publication in peer-reviewed journals.Trial registration number ISRCTN54765244; NCT0240168Cite Now